The bankers the next generation - Mayer, Martin (Truman Talley Books, 1997)
Introduces readers to what is enduring in the realm of money and what is transient; the social and economic fucntions banks perform and how these do or don't change; the current growth in credit cards and future smart cards; computer banking and the Internet; privacy and security; the flow of wholesale payments in the money markets, and the "notional" value of the derivatives, a rapidly growing source of profits for large banks.
Keywords: Bankwezen; Banques - États-Unis; Financiële instellingen; Services financiers - États-Unis; Bank; Banks and banking -- United States; Financial services industry -- United States; Kreditwesen; USA